IoT-Based Prototype for Parking Gate Security Monitoring and Customer Satisfaction Survey - Dhaniswara, Erwin; Subagiyo, Subagiyo; Mudjanarko, Sri Wiwoho; Mayestino, Alexander Machicky; Hidayat, Dwi Taufik; Talakua, Eddy Lybrech (NAROTAMA UNIVERSITY, 2025)
Digital transformation in parking systems is essential to improving operational efficiency, staff integrity, and customer satisfaction. PT Reska Multi Usaha (KAI Services) has implemented various technology-based parking systems such as Manless, Full Manless, Combo, and LPR. However, several locations still rely on manual supervision, which increases the risk of fraud and inaccurate overnight vehicle data. This study developed an Internet of Things (IoT)-based prototype system to monitor gate status and manage customer surveys automatically, with real-time data transmission to a centralized dashboard. The system utilizes gate position sensors, microcontrollers, and digital survey forms integrated with an online server. Test results show that the system operates effectively without manual input, with an average data latency of 1.57 seconds and sensor detection accuracy of up to 50 cm. The system has the potential to be integrated with the Early Warning System (EWS) Command Center to support safer and more responsive parking services.